2020
DOI: 10.1101/2020.04.04.20052092
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 diagnosis prediction in emergency care patients: a machine learning approach

Abstract: The coronavirus disease pandemic has increased the necessity of immediate clinical decisions and effective usage of healthcare resources. Currently, the most validated diagnosis test for COVID-19 (RT-PCR) is in shortage in most developing countries, which may increase infection rates and delay important preventive measures. The objective of this study was to predict the risk of positive COVID-19 diagnosis with machine learning, using as predictors only results from emergency care admission exams. We collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(77 citation statements)
references
References 8 publications
(12 reference statements)
3
73
0
1
Order By: Relevance
“…Our set of features performed as well as, or better than, the three diagnostic algorithms with the largest number of cases known to us at this time [12,13,16]. A report by Sun et al used epidemiologic, clinical, laboratory and imaging features in their algorithms and reported AUROCs of 0.91 (full model), 0.88 (without epidemiologic features), 0.88 (without imaging features), and 0.65 (with clinical features alone) [12].…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Our set of features performed as well as, or better than, the three diagnostic algorithms with the largest number of cases known to us at this time [12,13,16]. A report by Sun et al used epidemiologic, clinical, laboratory and imaging features in their algorithms and reported AUROCs of 0.91 (full model), 0.88 (without epidemiologic features), 0.88 (without imaging features), and 0.65 (with clinical features alone) [12].…”
Section: Discussionmentioning
confidence: 77%
“…Meng et al reported an AUROC of 0.89 using a different set of features that included activated partial thromboplastin time, triglycerides, uric acid, albumin/globulin, sodium, and calcium [16]. Batista et al developed an algorithm aimed for use in lower resource settings and reported an AUROC of 0.87 in a sparser dataset that only included basic demographics and complete blood cell counts [13]. In fact, our model which incorporated inflammatory markers significantly improved upon this set of features in terms of both AUROC and AUPRC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we identified a set of variables that may help differentiate COVID‐19 cases from other diseases. The model obtained exhibited an excellent AUC in the SP/RJ dataset comparable to more complex tools, including imaging and laboratory tests [11, 17–19]. This is impressive, considering that it is based solely on variables collected by the surveillance system.…”
Section: Discussionmentioning
confidence: 95%